Establishment of a secondary screening assay for P/Q-type calcium channel blockers - Hermann, David; Mezler, Mario; Swensen, Andrew M.; Bruehl, Claus; Obergrußerger, Ali; Wicke, Karsten; Schoemaker, Hans; Gross, Gerhard; Draguhn, Andreas; Nimmrich, Volker (Combinatorial chemistry & high throughput screening, 2013)
Development of calcium channel blockers is attractive, but has in the past been hampered by lack of high throughput electrophysiological technology. This limitation has been overcome by the implementation of automated patch clamp systems that allow identification of state-dependent compounds, which preferentially target pathologically overactive channels. We recently presented a fluorescence-based high-throughput screen for P/Q-type calcium channels followed by automated electrophysiology. Here, we provide a detailed description of the development of the secondary screen, and show the full analysis of the inactivation kinetics of the recombinant P/Q channel that served as a basis for the automated patch clamp protocol. Increasing the length of pre-depolarization shifted the inactivation to more hyperpolarized potentials. No steady-state inactivation was reached up to pre-depolarization durations of 3 min, while stability of the recordings progressively declined. As a compromise, a 3s pre-depolarization protocol was proposed for functional screening. In order to validate the electrophysiological screening, we compared kinetics and pharmacology of recombinant P/Q-type channels between automated and manual patch clamp measurements. Channel activation was similar under both conditions. By contrast, inactivation occurred at more hyperpolarized potentials in the automated system. Therefore, P/Q-type calcium channel inactivation is sensitive to the applied technological platform and needs to be adjusted when performing automated patch clamp recordings. Our results indicate that a thorough analysis of the inactivation kinetics is mandatory, when establishing an electrophysiological screening protocol for calcium channel blockers. As some data obtained by automated recordings may not be identical to manual patch clamp analysis, we recommend a proper initial validation of the screening assay and--if necessary--a posthoc adjustment of automated patch clamp values. The protocol presented here supports hit-to-lead and lead optimization efforts during the development of novel P/Q-type calcium channel blockers, and may be valuable for the generation of assays in other ion channel programs.